2017
DOI: 10.1073/pnas.1607226113
|View full text |Cite
|
Sign up to set email alerts
|

Long-wavelength fluctuations and the glass transition in two dimensions and three dimensions

Abstract: Phase transitions significantly differ between 2D and 3D systems, but the influence of dimensionality on the glass transition is unresolved. We use microscopy to study colloidal systems as they approach their glass transitions at high concentrations and find differences between two dimensions and three dimensions. We find that, in two dimensions, particles can undergo large displacements without changing their position relative to their neighbors, in contrast with three dimensions. This is related to Mermin-Wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
140
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(167 citation statements)
references
References 42 publications
24
140
0
3
Order By: Relevance
“…On a local scale, Mermin-Wagner fluctuations do not change the cage-escape process, and thus the microscopic mechanism of 2D and 3D glass transitions are not necessarily different. Recent work by Vivek et al using cage-relative intermediate scattering functions support this idea (31), and computer simulations by Shiba et al independently found similar results (32). Fig.…”
Section: Significancementioning
confidence: 78%
“…On a local scale, Mermin-Wagner fluctuations do not change the cage-escape process, and thus the microscopic mechanism of 2D and 3D glass transitions are not necessarily different. Recent work by Vivek et al using cage-relative intermediate scattering functions support this idea (31), and computer simulations by Shiba et al independently found similar results (32). Fig.…”
Section: Significancementioning
confidence: 78%
“…New theoretical tools and predictions do emerge, new phenomena are unveiled, and clever experiments are nonetheless carried out. In this vein, the two recent experimental papers in PNAS by Vivek et al (1) and Illing et al (2) convincingly address an issue at the junction of two fundamental questions in glass physics: the role of the dimensionality of space on the glass transition and the possible existence of long-wavelength fluctuations in 2D amorphous solids.…”
mentioning
confidence: 98%
“…They are also stimulating as they raise new questions and open avenues for further experimental and numerical investigations. Among the fundamental issues triggered by the studies in Vivek et al and Illing et al (1,2) are the theoretical foundations of these Mermin-Wagner fluctuations in 2D glassformers and the possible interference with other types of fluctuations. As stressed above, the observed glass transition is not a bona fide phase transition and notions such as rigidity and solidity for glasses still require some more robust theoretical underpinning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the glass transition from supercooled liquids to amorphous solids, the dimensionality dependence of the fluctuation has become an issue only recently. Gigantic fluctuation in 2D supercooled liquids has been observed that is far stronger than that in their 3D counterparts [10][11][12]. The aim of this Letter is to elucidate the similarity of this fluctuation to that in crystals [13], and also to investigate the heterogeneous dynamics in both 2D and 3D systems.…”
mentioning
confidence: 99%